2012
DOI: 10.1089/ten.tec.2011.0353
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation Analysis: Effect of Quantification Procedures on the Study Outcome

Abstract: Quantification of the amount of newly formed bone is an essential part of bone regeneration studies. Histomorphometry, based on histological sections of plastic-embedded specimens, is the most frequently applied technique in this assessment. Before performing image analysis, a specific region of interest (ROI) has to be determined. Based on the histological procedure, different areas within the ROI can be discriminated and assigned to relevant tissue structures. However, in literature not much attention is pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…from the cortical endosteal surface towards the center of the medullary cavity, until reaching almost complete filling with transient trabecular mesh at the peak of the osteogenic phase. Subsequently, the bone trabeculae are subjected to osteoclastic resorption and replacement by new marrow, which is identical to the original tissue that was removed (the so-called second osteogenic phase) [35,36]. In rats, the entire process is completed within 35 days [2].…”
Section: Discussionmentioning
confidence: 99%
“…from the cortical endosteal surface towards the center of the medullary cavity, until reaching almost complete filling with transient trabecular mesh at the peak of the osteogenic phase. Subsequently, the bone trabeculae are subjected to osteoclastic resorption and replacement by new marrow, which is identical to the original tissue that was removed (the so-called second osteogenic phase) [35,36]. In rats, the entire process is completed within 35 days [2].…”
Section: Discussionmentioning
confidence: 99%
“…Using different filters on the light microscope, pictures could be made of the fluorescent labels at the four different time points. Quantitative assessment of the pMMA specimens was performed using ImageJ computer‐based image analysis software (Java ® ImageJ 1.47, Image processing and analysis in Java) . From digitalized images of the sections (magnification: 5×), a circular region of interest (ROI) with a diameter equal to the created defects was positioned.…”
Section: Methodsmentioning
confidence: 99%
“…Examination of the PMMA sections revealed that both CPC/PLGA formulations were still present within the intramedullary cavity at the end of the 12 weeks implantation time. Due to the high density of the CPC/PLGA composite material, the relative thickness of PMMA sections and artifacts caused by staining, analysis of bone formation using PMMA embedding is inaccurate (Lopez‐Heredia et al ., ). In contrast, H&E and EVG staining of decalcified paraffin sections indicated the presence of abundant bone formation within the CPC matrix.…”
Section: Discussionmentioning
confidence: 97%